Monitoring Biodiversitas Kupu-Kupu di Perkebunan Jeruk Limau (Citrus amblycarpa) Berbasis Citizen Science - Ipin Aripin; Topik Hidayat; Nuryani Rustaman; Riandi Riandi (UIN Sunan Gunung Djati Bandung, 2021)
Citizen Science (CS) activities are currently a new trend in science gathering and research. Butterflies have an essential role as pollinator insects whose existence is currently under threat of population decline. CS activities can be a means to identify butterfly species in an area and take conservation actions. This study monitors butterfly biodiversity in lime plantations in Sindanghaji Village, Palasah District, Majalengka Regency through CS activities. This study involved (n=14) students who contracted conservation biology courses at Majalengka University. A sampling of butterflies was carried out in two areas of the lime (Citrus amblycarpa) plantation. Butterfly biodiversity data collection uses the swiping method and the total count technique. Identification of butterflies using the key of determination involves citizen scientists and comparisons on databases available at http://ftp.funet.fi/ and https://www.discoverlife.org/. The data analysis technique used quantitative methods with the help of the PAST (Paleontological statistics) application. The results showed that in garden area 1, there were 5 families, 18 genera, and 32 species with a total of 92 individuals; dominance index 0.936; the species diversity index is 3.065, the species evenness index is 0.691, and the species richness index is 6.635. As for garden 2, there are 5 families, 22 genera, and 38 species with a total of 175 individuals; dominance index 0.949; the species diversity index is 3.294, the species evenness index is 0.709, and the species richness index is 7.164. Based on the research, it can be concluded that the diversity of butterfly species in both areas is high, but no butterfly species dominates, so that the distribution is evenly distributed for each species. CS activities can be a solution in collecting, analyzing, and publishing research data on butterfly biodiversity.